Parametric Study of the Effect of Ground Anchor on Deep Excavation Stability - Aditya Putra Pratama; Hary Christady Hardyatmo; Fikri Faris (Journal of the Civil Engineering Forum, 2020)
Apartment construction is mostly carried out by including deep excavation works. However, excavation causes land instability; hence, the work needs to be done by a particular handler. In some cases, deep excavation is carried out on soft soil, which has a very high level of soil instability; therefore, a specific handling method such as ground anchor is required as an alternative. This study aims to conduct parametric research on the effect of using anchors on the stability of deep excavation. First, anchors of various slopes were modelled while varying the number of anchors up to four pieces. From the results of the study, the requirements representing the most efficient use of anchors were selected, and then various anchor bond lengths were modelled. Finally, the effect of applying various magnitudes of prestress forces to the anchor was determined. All of the models were examined to determine the influence on the stability of the deep excavation by observing the horizontal displacement and the forces that occur on the secant pile. From the analysis results, it can be concluded that the most effective slope angle is 0°. The displacement and forces occurred in the secant piles on the use of two, three, or four anchors has not a significant difference. The application of a higher prestress force on the anchor would yield better results as long as it is not exceeding 200 kN. However, in the case of an apartment building’s plans in Surabaya, the optimal anchor usage was found to be the use of two anchors with a 45° slope, 4.5 m for the first (A) and second (B) anchor bond lengths, 15 m free length anchor, 2.5 m vertical anchor distance, 1.2 m horizontal anchor distance, and the application of 200 kN prestress force.